2020
DOI: 10.1101/2020.06.03.131441
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Context-dependent functional compensation between Ythdf m6A readers

Abstract: 15The N6-methyladenosine (m 6 A) modification is the most prevalent post-transcriptional mRNA 16 modification, regulating mRNA decay, translation and splicing. It plays a major role during normal 17 development, differentiation, and disease progression. The modification is dynamically regulated 18 by a set of writer, eraser and reader proteins. The YTH-domain family of proteins: Ythdf1, Ythdf2, 19and Ythdf3, are three homologous m 6 A binding proteins, which have different cellular functions. 20However, their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 57 publications
2
57
0
Order By: Relevance
“…Further highlighting the complexity of these multifaceted regulatory mechanisms and underlining the need for future studies to fully unravel the molecular details, is the fact that two recent studies have proposed that YTHDF proteins function more similarly in the regulation of gene expression than previously described (Lasman et al , 2020; Zaccara & Jaffrey, 2020). Zaccara and Jaffrey report that in HeLa cells, YTHDF proteins all promote RNA decay, share common binding sites on mRNAs, and share similar protein interaction partners and subcellular localizations.…”
Section: Introductionmentioning
confidence: 99%
“…Further highlighting the complexity of these multifaceted regulatory mechanisms and underlining the need for future studies to fully unravel the molecular details, is the fact that two recent studies have proposed that YTHDF proteins function more similarly in the regulation of gene expression than previously described (Lasman et al , 2020; Zaccara & Jaffrey, 2020). Zaccara and Jaffrey report that in HeLa cells, YTHDF proteins all promote RNA decay, share common binding sites on mRNAs, and share similar protein interaction partners and subcellular localizations.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has demonstrated that the majority of the effects of m 6 A is mediated through a reduction in transcript stability 16,45 . Given this, one would expect that we would see an increase in expression of the highly methylated AR pathways genes ( Figure 2D), and therefore AR signaling, with METTL3 knockdown.…”
Section: Mettl3 Knockdown Triggers Ar-independencementioning
confidence: 99%
“…[ 61 ] YTHDF3, which has been less well studied than YTHDF1 and YTHDF2, appears to have dual roles in promoting degradation and translation in concert with YTHDF1 and YTHDF2. [ 38,39 ] While the aforementioned work has established a model whereby YTHDF proteins have distinct biological roles, two recent studies from Jaffrey [ 62 ] and Hanna [ 63 ] have called this model into question by proposing that YTHDF1/2/3 proteins are functionally redundant and all mediate mRNA decay but have no role in mRNA translation. The recent work, which includes both independent experiments and re‐analysis of previously published data, stands in sharp contrast to previous studies, particularly regarding the finding that YTHDF1/3 do not promote mRNA translation.…”
Section: Protein Readers Of Epitranscriptomic Modificationsmentioning
confidence: 99%
“…[38,39] While the aforementioned work has established a model whereby YTHDF proteins have distinct biological roles, two F I G U R E 2 Protein readers of epitranscriptomic modifications. Different reader proteins bind to m 6 A, m 5 C, and m 1 A and regulate cellular fate of modified RNAs recent studies from Jaffrey [62] and Hanna [63] have called this model into question by proposing that YTHDF1/2/3 proteins are functionally redundant and all mediate mRNA decay but have no role in mRNA translation. The recent work, which includes both independent experiments and re-analysis of previously published data, stands in sharp contrast to previous studies, particularly regarding the finding that YTHDF1/3 do not promote mRNA translation.…”
Section: Protein Readers Of Epitranscriptomic Modificationsmentioning
confidence: 99%